OVICIDAL ACTIVITY OF Syzygium aromaticum, Cinnamonam cassia, Carum carvi AND Citrus aurantium PLANT VOLTALIE OIL AGAINST THE PULSE BEETLE Callosobruchus maculatus - SASIKALA, J.; ELUMALAI, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
In the present study of ovicidal activity of S. aromaticum tested against the freshly laid eggs of Callosobruchus maculatus was tested in a environment laboratory. The plant voltile oil indicates that 50 mg/mL concentration of S. aromaticum oil-induced 16.00. 24.00 and 35.00% egg mortality when exposed to 24, 48 and 72 hrs exposure periods respectively. Similarly, the 100 mg/mL concentration of S. aromaticum oil-induced the egg mortality of 23.00. 49.00 and 43.00% when exposed to 24, 48 and 72 hrs exposure periods respectivel in 150 mg/mL concentration of S. aromaticum oil-induced the egg mortality of 35.00. 48.00 and 49.00% when exposed to 24, 48, and 72 hrs exposure periods. Remarkably, the 200 mg/mL concentration of S. aromaticum oil showed the ovicidal activity of 45.00. 52.00 and 56.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. The ovicidal activity of C. cassia tested against the freshly laid eggs of C. maculatus was tested, and indicates that 50 mg/mL concentration of C. cassia oil-induced 14.00.25.00 and 36.00% egg mortality when exposed to 24, 48 and 72 hrs exposure periods, respectively. Similarly, the 100 mg/mL concentration of C. cassia oil-induced the egg mortality of 24.00. 31.00 and 42.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. Besides, the 150 mg/mL concentration of C. cassia oil-induced the egg mortality of 30.00. 38.00 and 51.00% when exposed to 24, 48 and 72 hrs exposure periods. Remarkably, the 200 mg/mL concentration of C. cassia oil showed the ovicidal activity of 41.00. 45.00 and 54.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. The ovicidal activity of Ca. carvi tested against the freshly laid eggs of C. maculatus was tested and the data indicates that 50 mg/mL concentration of C. cassia oil-induced 18.00.26.00 and 33.00% egg mortality when exposed to 24, 48 and 72 hrs exposure periods, respectively in 100 mg/mL concentration of C. cassia oil-induced the egg mortality of 29.00. 37.00 and 46.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. Besides, the 150 mg/mL concentration of C. cassia oil-induced the egg mortality of 38.00. 46.00 and 53.00% when exposed to 24, 48 and 72 hrs exposure periods. Remarkably, the 200 mg/mL concentration of C. cassia oil showed the ovicidal activity of 50.00. 59.00 and 68.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. Ovicidal activity of Ci. aurantium tested against the freshly laid eggs of C. maculatus was tested and the data indicates that 50 mg/mL concentration of Ci. aurantium oil-induced 11.00 20.00 and 32.00% egg mortality when exposed to 24, 48 and 72 hrs exposure periods respectively in 100 mg/ml concentration of C. cassia oil-induced the egg mortality of 25.00. 28.00 and 42.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. Besides, the 150 mg/mL concentration of Ci. aurantium oil-induced the egg mortality of 37.00. 32.00 and 49.00% when exposed to 24, 48 and 72 hrs exposure periods. Remarkably, the 200 mg/mL concentration of Ci. aurantium oil showed the ovicidal activity of 40.00. 44.00 and 50.00% when exposed to 24, 48 and 72 hrs exposure periods respectively. Thus, it is possibly the infestation of the pest is phytochemical are safer for the environment.